Albatross and petrel overlap with pelagic longline fisheries in the Eastern Pacific Ocean - Daniel P. Crear; Thomas A. Clay; Ana P.B. Carneiro; Johannes H. Fischer; Igor Debski; David J. Anderson; Jill A. Awkerman; Alastair M.M. Baylis; Elizabeth A. Bell; Letizia Campioni; Paulo Catry; Tyler Clavelle; et al. (Fisheries Research, 2026)

Broad-scale pesticide screening finds anticoagulant rodenticide and legacy pesticides in Australian frogs - Jodi J.L. Rowley; Andrew Symons; Christopher Doyle; Jane Hall; Karrie Rose; Laura Stapp; Damian C. Lettoof (Science of The Total Environment, 2024)

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

Shell disease syndromes of decapod crustaceans - Andrew F. Rowley; Christopher J. Coates (Environmental Microbiology, 2023)
The term shell disease subsumes a number of debilitating conditions affecting the outer integument (the carapace) of decapod crustaceans, such as lobsters and crabs. Herein, we seek to find commonality in the aetiology and pathology of such conditions, and those cases that result in the progressive erosion of the cuticle through to the visceral tissues by a cocktail of microbial‐derived enzymes including lipases, proteases and chitinases. Aquimarina spp. are involved in shell disease in many different crustaceans across a wide geographical area, but the overall view is that the condition is polymicrobial in nature leading to dysbiosis within the microbial consortium of the damaged cuticle. The role of environment, decapod behaviour and physiology in triggering this disease is also reviewed. Finally, we provide a conceptual model for disease aetiology and suggest several avenues for future research that could improve our understanding of how such factors trigger, or exacerbate, this condition.

Invasive slipper limpets (Crepidula fornicata) act like a sink, rather than source, of Vibrio spp. - Emma A. Quinn; Sophie H. Malkin; Jessica E. Thomas; Ryan Poole; Charlotte E. Davies; Andrew F. Rowley; Christopher J. Coates (Biological Invasions, 2022)
A large knowledge gap exists regarding the disease profile and pathologic condition of the invasive, slipper limpet Crepidula fornicata . To help address this, we performed a year-long health survey at two sites in South Wales, UK – subtidal Swansea Bay and intertidal Milford Haven. In total, 1,800 limpets were screened systematically for haemolymph bacterial burdens using both general and vibrio-selective growth media (TSA + 2% NaCl and TCBS, respectively), haemolymph (blood) inspection using microscopy, a PCR-based assay targeting Vibrio spp., and multi-tissue histology. Over 99% of haemolymph samples contained cultivable bacterial colony-forming units, and 83% of limpets tested positive for the presence of vibrios via PCR (confirmed via Sanger sequencing). Vibrio presence did not vary greatly between sites, yet a strong seasonal effect was observed with significantly higher bacterial loads during the summer. Binomial logistic regression models revealed larger (older) limpets were more likely to harbour vibrios, and the growth of bacteria on TCBS was a key predictor for PCR-based vibrio detection. Histological assessment of > 340 animals revealed little evidence of inflammation, sepsis or immune reactivity despite the gross bacterial numbers. We contend that slipper limpets are not highly susceptible to bacteriosis at either site, and do not harbour vibrios known to be pathogenic to humans. The lack of susceptibility to local pathogenic bacteria may explain, in part, the invasion success of C. fornicata across this region.

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

A pathogenic deletion in Forkhead Box L1 (FOXL1) identifies the first otosclerosis (OTSC) gene - Nelly Abdelfatah; Ahmed A. Mostafa; Curtis R. French; Lance P. Doucette; Cindy Penney; Matthew B. Lucas; Anne Griffin; Valerie Booth; Christopher Rowley; Jessica E. Besaw; Lisbeth Tranebjærg; Nanna Dahl Rendtorff; et al. (Human Genetics, 2022)
Otosclerosis is a bone disorder of the otic capsule and common form of late-onset hearing impairment. Considered a complex disease, little is known about its pathogenesis. Over the past 20 years, ten autosomal dominant loci ( OTSC1-10 ) have been mapped but no genes identified. Herein, we map a new OTSC locus to a 9.96 Mb region within the FOX gene cluster on 16q24.1 and identify a 15 bp coding deletion in Forkhead Box L1 co-segregating with otosclerosis in a Caucasian family. Pre-operative phenotype ranges from moderate to severe hearing loss to profound sensorineural loss requiring a cochlear implant. Mutant FOXL1 is both transcribed and translated and correctly locates to the cell nucleus. However, the deletion of 5 residues in the C-terminus of mutant FOXL1 causes a complete loss of transcriptional activity due to loss of secondary (alpha helix) structure. FOXL1 (rs764026385) was identified in a second unrelated case on a shared background. We conclude that FOXL1 (rs764026385) is pathogenic and causes autosomal dominant otosclerosis and propose a key inhibitory role for wildtype Foxl1 in bone remodelling in the otic capsule. New insights into the molecular pathology of otosclerosis from this study provide molecular targets for non-invasive therapeutic interventions.

Antagonistic Activity of Lactic Acid Bacteria Against Pathogenic Vibrios and Their Potential Use as Probiotics in Shrimp (Penaeus vannamei) Culture - John Thompson; Mark A. Weaver; Ingrid Lupatsch; Robin J. Shields; Sue Plummer; Christopher J. Coates; Andrew F. Rowley (Frontiers in Marine Science, 2022)
Probiotic use in aquaculture settings can be an approach for disease control and dietary supplementation. We assessed the antagonistic effect of culture supernatants of lactic acid bacteria on the growth of known shrimp pathogens, Vibrio ( Listonella ) anguillarum , Vibrio alginolyticus , and V. harveyi , using a quantitative microplate bioassay. Supernatants from Lactobacillus curvatus subsp. curvatus, L. plantarum , and Pediococcus acidolactici significantly inhibited the growth of these vibrios. The active component(s) were heat stable (> 100°C) and resistant to freeze-thawing. Most of this inhibitory activity was brought about by the production of an acid pH; however, there was evidence for other factors playing a role. In the search for novel probiotic bacteria, an organism was isolated from the gastrointestinal tract of healthy whiteleg shrimp ( Penaeus vannamei)— identified tentatively as Carnobacterium maltaromaticum . This isolate, however, had less potent vibriocidal activity than the lactic acid bacteria and reduced shrimp survival at a dose of 1 × 10 7 bacteria/shrimp. During a 28-day feeding trial, juvenile P. vannamei fed with L. plantarum supplemented diets showed no gross changes in growth parameters compared with the control. We suggest that lactic acid bacteria could be incorporated into biofloc formulations to purge the growth of pathogenic vibrios in pond settings, rather than being fed directly to shrimp.

Emerging Diseases and Epizootics in Crabs Under Cultivation - Christopher J. Coates; Andrew F. Rowley (Frontiers in Marine Science, 2022)
While most crab production for human consumption worldwide comes from capture fisheries, there is increasing production of selected species using aquaculture-based methods. This is both for the purpose of stock replacement and direct yield for human consumption. Disease has limited the ability to produce larval crabs in commercial hatcheries and this together with suitable feeds, are major hurdles in the sustainable development of cultivation methods. Juvenile and adult crabs are also subject to a range of diseases that can cause severe economic loss. Emerging pathogens/parasites are of major importance to crab aquaculture as they can cause high levels of mortality and are difficult to control. Diseases caused by viruses and bacteria receive considerable attention but the dinoflagellate parasites, Hematodinium spp., also warrant concern because of their wide host range and lack of control methods to limit their spread. This concise review examines the emerging diseases in several crabs that have been selected as candidates for aquaculture efforts including Chinese mitten crabs ( Eriocheir sinensis ), mud crabs ( Scylla spp.), swimming crabs ( Portunus spp.), blue crabs ( Callinectes sapidus ) and shore crabs ( Carcinus maenas ). The latter is also a prolific invasive species known to harbour diverse macro- and micro-parasites that can affect commercially important bivalves and crustaceans.

The diarrhetic shellfish-poisoning toxin, okadaic acid, provokes gastropathy, dysbiosis and susceptibility to bacterial infection in a non-rodent bioassay, Galleria mellonella - Helena Emery; William Traves; Andrew F. Rowley; Christopher J. Coates (Archives of Toxicology, 2021)
Diarrhetic shellfish-poisoning (DSP) toxins such as okadaic acid and dinophysistoxins harm the human gastrointestinal tract, and therefore, their levels are regulated to an upper limit of 160 μg per kg tissue to protect consumers. Rodents are used routinely for risk assessment and studies concerning mechanisms of toxicity, but there is a general move toward reducing and replacing vertebrates for these bioassays. We have adopted insect larvae of the wax moth Galleria mellonella as a surrogate toxicology model. We treated larvae with environmentally relevant doses of okadaic acid (80–400 μg/kg) via intrahaemocoelic injection or gavage to determine marine toxin-related health decline: (1) whether pre-exposure to a sub-lethal dose of toxin (80 μg/kg) enhances susceptibility to bacterial infection, or (2) alters tissue pathology and bacterial community (microbiome) composition of the midgut. A sub-lethal dose of okadaic acid (80 μg/kg) followed 24 h later by bacterial inoculation (2 × 10 5 Escherichia coli ) reduced larval survival levels to 47%, when compared to toxin (90%) or microbial challenge (73%) alone. Histological analysis of the midgut depicted varying levels of tissue disruption, including nuclear aberrations associated with cell death (karyorrhexis, pyknosis), loss of organ architecture, and gross epithelial displacement into the lumen. Moreover, okadaic acid presence in the midgut coincided with a shift in the resident bacterial population over time in that substantial reductions in diversity (Shannon) and richness (Chao-1) indices were observed at 240 μg toxin per kg. Okadaic acid-induced deterioration of the insect alimentary canal resembles those changes reported for rodent bioassays.

Indomethacin-induced gut damage in a surrogate insect model, Galleria mellonella - Helena Emery; Richard Johnston; Andrew F. Rowley; Christopher J. Coates (Archives of Toxicology, 2019)

Posteromedial hyperactivation during episodic recognition among people with memory decline: findings from the WRAP study - Christopher R. Nicholas; Ozioma C. Okonkwo; Barbara B. Bendlin; Jennifer M. Oh; Sanjay Asthana; Howard A. Rowley; Bruce Hermann; Mark A. Sager; Sterling C. Johnson (Brain Imaging and Behavior, 2015)